DAMPAK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH INKLUSI DAN SEKOLAH LUAR BIASA - Nuraini Nuraini (ADIBA : JOURNAL OF EDUCATION, 2023)
School is a place to socialize and learn. Schools are educational institutions that train students' character building and facilitate students to grow and explore student potential so that they can produce generations that are productive, creative, and able to answer challenges. The implications for school institutions that can be seen directly are inclusive schools, institutions that are able to overcome discrimination effectively, create friendly communication, and form an inclusive society to realize educational goals. The available SLBs are quite well-established, have adequate facilities and infrastructure, adequately representative equipment and buildings, sufficiently professional staff, and have strong legality institutionally. The community is a user of educational institutions with the existence of an inclusive school which will facilitate community access to send their children to the nearest school because there is only one special school such as an SLB and it is in the district capital. provide treatment to children with special needs because they have experts in their fields and have teachers who are graduates from PLB.